Non-apoptotic roles of apoptotic proteases: new tricks for an old dog - Tin Tin Su (Open Biology, 2020)
This Open Question article highlights current advances in the study of non-apoptotic roles of apoptotic proteins. Apoptosis is a highly regulated and energy-requiring process in which cells actively kill themselves. Apoptosis helps remove extra cells to sculpt organs during embryo development and culls damaged cells throughout the body. Apoptosis relies on evolutionarily conserved proteins that include a family of proteases called caspases. Caspases activity has long been considered a hallmark of apoptosis. Yet an emerging body of literature indicates that caspase activity is required for a number of non-lethal processes that range from sculpting cells, removing protein aggregates, changing cell identity during differentiation or de-differentiation, and rebuilding tissues. Failure in each of these processes is associated with human disease. This article is not meant to be an exhaustive review but an introduction to the subject for an educated public, with caspases as a gateway example. I propose that it is time to explore non-apoptotic roles of caspases and other apoptotic proteins, in order to better understand their non-apoptosis function and to leverage new knowledge into new therapies.